RIFAMPIN-INDUCED ADRENAL CRISIS - Yee, Teh When; Mathews, Gerard Jason; Subramaniam, Seetha Devi; Abdullah, Noor Rafhati Adyani; Merican, Nor Shaffinaz Yusoff Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Rifampicin is an essential first-line anti-tuberculosis drug. It is crucial for medical practitioners practicing in countries such as Malaysia where tuberculosis is endemic to recognize that rifampicin, an enzyme inducer, can have serious drugdrug interactions and needs to be used cautiously. CASE We describe a case of a 30-year-old male who sustained a mild traumatic brain injury with cerebrospinal fluid leakage in 2022. His injury was complicated by panhypopituitarism and secondary adrenal insufficiency, which required hydrocortisone 10mg/5mg BD and desmopressin replacement. He was compliant to hormonal replacement and remained asymptomatic throughout regular follow-up. In February 2024, he presented with submandibular swelling that turned out to be tuberculous lymphadenitis with pulmonary tuberculosis. He was started on first-line antituberculosis medications (Akurit-4), containing rifampicin, isoniazid, pyrazinamide and ethambutol with his usual dose of hydrocortisone. Three days after the initiation of anti-tuberculosis medication, the patient presented with vomiting, fever with postural dizziness without polyuria. Blood pressure was 102/64 mmHg, with postural hypotension and hypoglycaemia. The patient was diagnosed with adrenal insufficiency secondary to rifampicin. The patient was started on intravenous hydrocortisone 50 mg QID. Laboratory investigations revealed serum cortisol of <27 nmol/L with adrenocorticotropic hormone level of 0.36 pmol/L. After adequate hydrocortisone replacement, the patient had polyuria with a gradual reduction of serum sodium to 125 mmol/L, unmasking the presence of central diabetes insipidus. Desmopressin was started and the patient clinically improved with normalisation of serum sodium. CONCLUSION In patients with pre-existing adrenal insufficiency, initiation of an anti-tuberculosis regimen containing rifampicin may increase the metabolism of cortisol by inducing cytochrome CYP3A4 activity and precipitate an adrenal crisis. Before initiation of anti-tuberculosis medications, drug-drug interaction should be reviewed. In such cases, dose adjustment of hydrocortisone is necessary to prevent adrenal insufficiency. Increasing the hydrocortisone dose gradually and close monitoring of the patient’s biochemical and clinical state are important to reduce the risk of adrenal crisis and mortality.